PEMBUATAN BIOETANOL DARI TEPUNG AMPAS TEBU MELALUI PROSES HIDROLISIS TERMAL DAN FERMENTASI: PENGARUH PH, JENIS RAGI, DAN WAKTU FERMENTASI - Irvan, Popphy Prawati, Bambang Trisakti (Jurnal Teknik Kimia USU, 2015)
Bioethanol is ethanol, which made from starch, glucose, or cellulose of plants. In this research, it has been made from cellulose of sugarcane baggase. This research was conducted to study about the effect of pH, yeast type and the duration of fermentation to yield’s ethanol. The main processes in this research were thermal hydrolysis by liquid hot water (LHW) method, fermentation by using  Saccharomyces cerevisiae and purification by vacuum distillation. The variables in this research were pH 4; 4,5; and 5; baker’s yeast and fermented glutinous cassava; and the duration of fermentation were 2, 4, 6, 8 and 10 days. Based on the analysis of the yield, the volume of bioethanol is 23 mL with 0,95 g/ml density and 161,59 kkal/kg heat value as the best yield, under the condition of  pH 5 and 4 days of the duration of fermentation using baker’s yeast.